Congenital toxoplasmosis: an observational retrospective study in the Eastern Sicily - Garozzo, Maria Teresa; Garozzo, Rosaria; Betta, Pasqua; Cilauro, Salvatore; Saporito, Alessandro; D'Amico, Pietro; Tina, Gabriella; Motta, Angela; Pulvirenti, Alfredo; Alaimo, Salvatore; Sciuto, Laura; Pecorino, Basilio; et al. (Frontiers in Pediatrics, 2025)
IntroductionToxoplasma gondii (T. gondii) primary infection during pregnancy can lead to severe consequences in the fetus and newborn, including miscarriage, congenital disease, or neuro-ophthalmological complications.ObjectivesThis study aimed to evaluate the incidence of congenital toxoplasmosis (CT) in a cohort of newborns and assess their neurological, ophthalmological, and auditory sequelae. Additionally, we examined correlations between infection rates, gestational age at maternal seroconversion, prenatal treatment, and postnatal outcomes.MethodsWe studied a cohort of 220 newborns evaluated for suspected CT between 2000 and 2021 across three hospitals in Catania, Italy. Prenatal screening identified 98.6% of maternal infections. Collected data included gestational history, neonatal clinical data, and follow-up assessments.ResultsMother-to-child transmission (MTCT) occurred in 19.2% (29/151) of cases with available follow-up data. MTCT rates increased significantly with gestational age at maternal seroconversion: 5% in the first trimester, 23% in the second, and 63% in the third (p < 0.001). Prenatal treatment administered for ≥28 days was associated with a significantly lower MTCT rate (11.8% vs. 28.6%, p = 0.037). No significant association was found between maternal age and the risk of transmission (OR = 1.38, 95% CI: 0.54–3.55; p = 0.635). Of the 29 infected newborns, 17 (58.6%) were symptomatic at birth and during the long-term follow-up. Manifestations included microcephaly (10%), intracranial abnormalities (19%), behavioral disturbances (4%), epilepsy (7%), and psychomotor delay (7%). Ophthalmological lesions were present in 21% at birth and 45% during follow-up; no cases of hearing loss were recorded. No significant correlation was observed between gestational age at seroconversion and the presence of clinical symptoms, ocular findings, or neurological sequelae.ConclusionsPrenatal screening is effective in identifying newborns at risk for CT who require close monitoring and treatment. While our findings align with literature regarding MTCT rates, they differ regarding symptomatic case correlations. Further studies are warranted to better understand the factors influencing disease progression and long-term outcomes.